Representation of Female Identity in Instapoetry: A Study of Works of German Female Poets on Instagram - Saksono, Lutfi; Suhartono, Suhartono; Kurniawati, Wisma (Proceeding of International Joint Conference on UNESA, 2025)
Instapoetry adalah bentuk puisi baru yang ditulis di intagram. Barisnya pendek dan kata-kata serta kalimatnya cukup sederhana. Awalnya instapoetry tidak dianggap sebagai sebuah karya, tetapi selanjutnya ada banyak orang yang menjadi popular dan meraih keuntungan finansial dari platform digital ini. Umumnya penulis instapoetry adalah perempuan dan anak muda. Di Jerman ada bebera perempuan yang telah menulis puisi di Instagram. Beberapa nama akun antara lain #kursives_ich dan #kursives_du, #aufdenpunkt, poeticadeni, enila_writes, _oneironautin and others. German female poets have addressed the themes of gender identity, and personal experiences. Seeing women as writers rather than readers is inseparable from Elaine Showalter’s concept of gynocriticism. Themes such as self-exploration, love, body, and digital space are evidence of women’s transformative process in asserting their identity amidst social and technological changes. Instapoetry is not only an art form, but also a tool for women’s liberation and resistance in the modern digital literary landscape. Elaine Showalter, through a gynocritic approach, emphasizes the importance of identifying and understanding women’s voices in literary works.